Young Workers with Disabilities and the Threat of Skill Traps Entering Job Opportunities (International Journal of Scientific Research and Management (IJSRM), 2023)
More than one billion people or 15 percent of the world’s population are people with disabilities. Participation of people with disabilities in the labor force is important to prevent a decline in overall labor force participation rates in the future. The threat of a "skill trap" befalls them, especially in the era of digitalization, where access to training is limited. With the higher cost of living, workforce accessibility for people with disabilities has become essential. The research aims to identify factors that influence the employment opportunities of young workers with disabilities, including marital status, education, gender, employment sector, number of household members, area of residence, and skills. A quantitative approach with a cross-sectional research design was used to analyze secondary data from the 2022 National Labor Force Survey. Data analysis used binary logistic regression with the dependent variable being employment status, and independent variables covering the personal and family characteristics of the respondents. The variables include gender, age, education level, family type, parents’ monthly income, parents’ education and employment, employment sector, number of household members, and area of residence. Research shows that marital status, education level, gender, and employment sector have a significant positive influence on the employment opportunities of young workers with disabilities. However, the number of household members and area of residence have a negative influence on employment opportunities. Improving the skills of people with disabilities has a positive impact, emphasizing the importance of skills development in increasing their accessibility in the labor market.